Mosquitoes: identification, ecology and control - Becker, Norbert; Petrić, Dušan; Zgomba, Marija; Boase, Clive; Madon, Minoo B.; Dahl, Christine; Kaiser, Achim (Springer, 2020)
PART I General Aspects -- Systematics -- Biology of Mosquitoes -- Medical Importance of Mosquitoes -- Mosquito Research Techniques.-Morphology of Mosquitoes -- PART II Identification Keys Morphology Ecology and Distribution of European Species -- Key to Female Mosquitoes -- Key to Male Mosquitoes -- Key to Mosquito IV Instar Larvae -- Subfamily Anophelinae -- Subfamily Culicinae -- PART III Identification Keys Morphology Ecology and Distribution of Important Vector and Nuisance Species World Wide -- Africa -- Asia -- Australia -- Central and South America -- North America -- PART IV Control of Mosquitoes -- Biological control -- Environmental management -- Chemical control -- Physical control -- Genetical control -- Personal protection -- Integration and implementation of mosquito management -- Literature.
Keywords: Stechmücken